(untitled) (قضايا سياسية, 2024)
This study examines multipolarity in international politics and economics, intending to enhance global order comprehension. The global order's evolution is examined through WWI, WWII, the Cold War, and globalization. Identifying international multipolarity patterns is highlighted. The research also investigates multipolar global economic system outcomes. Methodology: A multidisciplinary approach is used in this study, combining historical data and theoretical frameworks. The study analyses primary sources, scholarly literature, and empirical data to trace the world order's historical origins and identify important drivers of diversity. In addition, qualitative research methodologies are used to assess current world political and economic trends, providing global insights. Results: The data shows a clear shift towards multipolarity in the global arena. The study illustrates global order changes by examining WWI, WWII, the Cold War, and globalization trends. A multipolar environment is taking shape right now due to the increasing importance of several power centers and economic groups. Global government, economics, and geopolitics are all greatly influenced by this transition. Conclusion: This research concludes that multipolarity profoundly affects world affairs. The world is moving closer to a multipolar system, as shown by historical precedents and present trends. This dynamic environment necessitates that stakeholders and policymakers adjust by encouraging open communication, teamwork, and the global community. Accepting multipolarity helps the international community discuss the complexities and challenges of a multipolar global economic system, promoting global peace, stability, and prosperity